The Effectiveness of Construction Industry Development Board (CIDB) Green Card Training Program for Foreign Workers Towards Safety Performance at Nadayu Site - Nurhana Abd Wahab; Nik Hasnaa Nik Mahmood; Asnul Dahar Minghat (ASEAN Journal of Science and Engineering Education, 2023)
This paper focused on the impact of the Construction Industry Development Board (CIDB) Training Green Card Training program based on the general worker’s knowledge, behavior, and safety performance at the Nadayu site and also discovered the primary factors affecting CIDB Green Card Training Program. For this purpose, 55 workers filled up the questionnaire before and after attending the safety training. The effectiveness of the workers can be determined through the knowledge acquired from the training and can be evaluated from their behavior through observation by management personnel at the site. On top of that, the performance of safety at the site can be evaluated through the numbers of NCR, Memos, Penalties, and first aid. The results show that language and the background of participants were found to be the strongest factor that is affecting CIDB Green Card Training Program. Basic safety knowledge of participants has also increased after attending the training and improvement based on workers' behavior at the site were observed as well. Improvements need to be considered to enhance the CIDB Green Card Training program by providing training in the native language, screening the workers who have experience in the construction line in Malaysia, implementing various methods of teaching, presenting updated slide presentations, and evaluating participants to test their understanding.